RodentSQL: a software suite for colony management of animal protocols. (27th July 2018) - Pawar, Shrikant; Batra, Harshul
Aim: Animal experiments tend to generate large-scale data. Some existing tools like Microsoft Excel and colony management cloud-based tools are either cumbersome or expensive. There is a need for an inexpensive and uncomplicated colony management software with specific individual database solutions.Methods: We have developed a database application named RodentSQL to meet most of the requirements of such animal colony management programs.Results: We present a user-friendly secure system for managing records of phenotype, genotype and metadata for comprehensive data analysis and mining. RodentSQL can be altered based upon user needs. We have successfully tested its usage in beta users for managing data of hamsters and mice.Conclusion: A central facility can share and benefit from this colony management system. RodentSQL can increase workflow efficiency and data security leading to significant cost savings and enhanced scientific results. RodentSQL is offered to the scientific community as an open source software. Lay abstract: Animal experiments tend to generate large-scale data. Some existing tools like Microsoft ® Excel (WA, USA) and colony management cloud-based tools are either cumbersome or expensive. Addressing this concern, we have developed a database application named RodentSQL to meet most of the requirements of such animal colony management programs, which can lead to significant cost savings and enhanced scientific results.